Differential Effects of Varying Concentrations of Phosphorus, Iron, and Nitrogen in N2-Fixing Cyanobacteria - Fernández-Juárez, Víctor; Bennasar-Figueras, Antoni; Sureda-Gomila, Antoni; Ramis-Munar, Guillem; Agawin, Nona S. R. (Frontiers in Microbiology, 2020)
Diazotrophs or N2-fixers are one of the most ecologically significant groups in marine ecosystems (pelagic and benthic). Inorganic phosphorus (PO43-) and iron (Fe) can limit the growth and N2-fixing capacities of cyanobacteria. However, studies investigating co-limitation of these factors are lacking. Here, we added different concentrations of PO43- and Fe in two cyanobacterial species whose relatives can be found in seagrass habitats: the unicellular Halothece sp. (PCC 7418) and the filamentous Fischerella muscicola (PCC 73103), grown under different nitrate (NO3-) concentrations and under N2 as sole N source, respectively. Their growth, pigment content, N2-fixation rates, oxidative stress responses and morphological and cellular changes were investigated. Our results show serial limitation of NO3- and PO43- (with NO3- as the primary limiting nutrient) for Halothece sp. Simultaneous co-limitation of PO43- and Fe were found for both species tested and high levels of Fe (specially when added with high PO43- levels) inhibited the growth of Halothece sp. Nutrient limitation (PO43-, Fe and/or NO3-) enhanced oxidative stress responses, morphological changes and apoptosis. Furthermore, an extensive bio-informatic analysis describing the predicted Pho, Fur and NtcA regulon (involved in the survival of cells to P, Fe and N-limitation) was made using the complete genome of Halothece sp. as a model, showing the potential of this strain to adapt to different nutrient regimes (P, Fe or N).